2021
DOI: 10.1074/jbc.ra120.016115
|View full text |Cite
|
Sign up to set email alerts
|

A second mechanism employed by artemisinins to suppress Plasmodium falciparum hinges on inhibition of hematin crystallization

Abstract: Malaria is a pervasive disease that affects millions of lives each year in equatorial regions of the world. During the erythrocytic phase of the parasite life cycle, Plasmodium falciparum invade red blood cells, where they catabolize hemoglobin and sequester the released toxic heme as innocuous hemozoin crystals. Artemisinin-class drugs are activated in vivo by newly-released heme, which creates a carbon-centered radical that markedly reduces parasite density. Radical damage to parasite lipids and proteins is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…A second mechanism, where a drug binds by adsorption mechanisms to the surface of growing β-hematin crystals and suppresses crystal elongation, also indicated that artemisinin does not interfere with β-hematin crystal elongation [35,39]. All these findings, validated by independent research groups [40,41], converged to the notion that antimalarial peroxides do not interfere with hematin mineralization. Subsequently, it became clear that the absence of β-hematin inhibitory activity for antimalarial peroxides is due to a lack of binding affinity of these drugs for hematin [9].…”
Section: Introduction To Heme Detoxificationmentioning
confidence: 75%
See 1 more Smart Citation
“…A second mechanism, where a drug binds by adsorption mechanisms to the surface of growing β-hematin crystals and suppresses crystal elongation, also indicated that artemisinin does not interfere with β-hematin crystal elongation [35,39]. All these findings, validated by independent research groups [40,41], converged to the notion that antimalarial peroxides do not interfere with hematin mineralization. Subsequently, it became clear that the absence of β-hematin inhibitory activity for antimalarial peroxides is due to a lack of binding affinity of these drugs for hematin [9].…”
Section: Introduction To Heme Detoxificationmentioning
confidence: 75%
“…Hung et al [43] made use of a radiolabeled artemisinin and protocols for extracting Hz to show that artemisinin treatment was associated with the Hz content, likely in the form of hematin-artemisinin adducts, denoting a possible fate of artemisinin to interact with Hz. However, using mass spectroscopy, two independent research groups were unable to identify endoperoxide and its hematin adducts adsorbed on Hz from parasites treated with artemisinin, artesunate or dihydroartemisinin in a concentration range from 500 to 5000 nM [41,44]. Importantly, dihydroartemisinin treatment at 5000 nM resulted in hematin-drug adducts widely associated with the parasite cell lysate but not detected in the Hz fraction [44].…”
Section: Introduction To Heme Detoxificationmentioning
confidence: 99%
“…As an example, in the antimalaria activity of these molecules, the two oxygens present in the peroxide group with their electron density is an attractive site for the iron positively charged in heme. Ma et al [ 15 ] had demonstrated that heme–drug adducts, produced after the radical activation of artemisinins, can inhibit β-hematin crystallization and heme detoxification, a pathway which complements the deleterious effect of radicals generated via parent drug activation.…”
Section: Discussionmentioning
confidence: 99%
“…AFM offers high content data for characterizing cell surfaces (Bhat et al, 2015), membranes and envelopes (Viljoen et al, 2020), cell division (Formosa et al, 2013;Bhat et al, 2018a) and adhesion (Mathelie-Guinlet et al, 2019). Systems studied by AFM range from viruses (Chen et al, 2013) to embryonic tissue (Chevalier et al, 2016;Thompson et al, 2019), parasites (Sinha et al, 2015;Perez-Guaita et al, 2018;Ma et al, 2020) and other pathogens (Alsteens et al, 2009;Deupree and Schoenfisch, 2009;Alsteens et al, 2013).…”
Section: Using Afm To Study Pathogens and Their Behaviormentioning
confidence: 99%